PENDIDIKAN MULTIKULTURAL DALAM PERSPEKTIF ISLAM: UPAYA PENGENALAN NILAI-NILAI ISLAM YANG UNIVERSAL KEPADA PESERTA DIDIK MELALUI DUNIA PENDIDIKAN - Muhammedi Muhammedi (Universitas Islam Negeri Sumatera Utara, 2016)
Multicultural education is a philosophy that emphasizes the significance, legitimacy and vitality of ethnic and cultural diversity in shaping the lives of individuals, groups and nations. Objectives of Islamic Education is multicultural education that respects and embraces all forms of diversity. Thus it can be expected to grow wisdom in seeing all forms of diversity that exists. Islam is perfect and complete. (Kamil-mutakamil). Therefore all aspects of life would have been discussed and disyari'atkan in it. Example of tolerance, dialogue and consultation, mutual help, silaturrahim, fraternity and others.Key word: education, multicultural, perspective, Islam